2016
DOI: 10.4103/2008-322x.183932
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of descemetopexy with isoexpansile perfluoropropane after cataract surgery

Abstract: Purpose:To report the indications, anatomical outcomes, functional outcomes and limitations of descemetopexy with intracameral injection of isoexpansile perfluoropropane (14% C3F8) in eyes with Descemet's membrane (DM) detachment after cataract surgery.Methods:This retrospective non-comparative interventional case series included 67 eyes of 67 patients who underwent descemetopexy at a tertiary eye hospital. The procedure consisted of descemet's membrane reattachment by injecting isoexpansile perfluoropropane (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…However, pneumodescemetopexy with C3F8 is not without complications. Studies have previously reported raised intraocular pressure (13.5%) and pupillary block glaucoma (11%) post pneumodescemetopexy with C3F8 [ 5 , 6 ]. Injection of a large amount of C3F8 can cause compression of the iris against the lens surface leading to iris ischemia and subsequent Urrets-Zavalia syndrome [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, pneumodescemetopexy with C3F8 is not without complications. Studies have previously reported raised intraocular pressure (13.5%) and pupillary block glaucoma (11%) post pneumodescemetopexy with C3F8 [ 5 , 6 ]. Injection of a large amount of C3F8 can cause compression of the iris against the lens surface leading to iris ischemia and subsequent Urrets-Zavalia syndrome [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Possible intraoperative complications are IOP rise due to pupillary block, inadvertent intrastromal gas injection, and injury to the lens. [5]…”
Section: Discussionmentioning
confidence: 99%
“…A successful surgical intervention reattaches a detached Descemet’s membrane (DM) and has been shown to enhance corneal deturgescence and recovery of visual function. Successful reattachment of DM has been reported with the intracameral use of air, viscoelastic substance and expansile gases including sulfur hexafluoride (SF6) and perfluoro propane (C3F8) 3. Several authors have reported air descemetopexy to be a safe and effective treatment option for DMD 3 4…”
Section: Introductionmentioning
confidence: 99%
“…Successful reattachment of DM has been reported with the intracameral use of air, viscoelastic substance and expansile gases including sulfur hexafluoride (SF6) and perfluoro propane (C3F8) 3. Several authors have reported air descemetopexy to be a safe and effective treatment option for DMD 3 4…”
Section: Introductionmentioning
confidence: 99%